Can artificial rearing benefit the natural breeding of European pond turtle (Emys orbicularis) in its northern distribution range? - Vytautas Rakauskas; Kristė Stravinskaitė; Rasa Jautakienė; Jonas Šimkus; Inga Čitavičienė; Alma Pikunienė; Gintarė Stankevičė; Eglė Šidagytė-Copilas (Acta Herpetologica)
The European Pond turtle (Emys orbicularis, L., 1758) is protected and endangered species in Europe. However, in some of the countries it is already extinct. In Lithuania E. orbicularis populations are very small and highly fragmented therefore very vulnerable and declining. The main reasons of such E. orbicularis populations decrease are habitat loss due to the changes in land use and destruction of nesting sites. Saving local populations needs active species protection measures. Previous studies showed E. orbicularis individuals are vulnerable in all stages of life, but the most exposed are early life stages: incubation of eggs and first overwintering of hatchlings. The aim of this study was to compare hatching success of naturally vs artificially incubated E. orbicularis eggs and further artificially reared hatchlings survival during their first year. Furthermore, a perennial detail description of the main nesting measurements (clutch size, depth) was provided from the small E. orbicularis populations in its northern distribution range, Lithuania. Finally, a detail description of approved artificial egg incubation and further hatchlings rearing methodology is provided. The provided methodologies for artificial E. orbicularis incubation and further rearing may be used to preserve and increase the size of local small E. orbicularis populations in its northern distribution range.